Verbal Aggression: Linguistic and Legal Aspect (Law and Safety, 2025)
The article examines the phenomenon of verbal aggression as a linguistic and legal problem which, under certain conditions, can be qualified as an administrative or criminal offence. The verbal aggression is defined as a conscious communicative strategy aimed at achieving certain goals through the use of language. Theoretical aspects of communication strategies are characterised. The key characteristics, forms of manifestation and consequences of verbal aggression in the context of interpersonal communication are analysed. Various forms of verbal aggression are considered, including insults, threats, criticism, irony, manipulation and ignoring. Particular attention is paid to the analysis of linguistic means used to implement verbal aggression as a communication strategy. The lexical, syntactic and stylistic features of aggressive statements, as well as their impact on the emotional state of the interlocutor are identified.The term “offence committed verbally” in the context of legal linguistics is considered, and its difference from more established concepts such as “hate speech” or “verbal aggression” is emphasised. It is noted that the development of jurisprudence contributes to a detailed analysis of speech actions that may have legal significance.The main attention is paid to the characterization of offences committed verbally through the components of their legal qualification, in particular, the object, objective side, subject and subjective side. The public danger associated with their information impact on public relations, in particular, human rights, public order, state security and interests of justice, is considered. The linguistic expertise is analysed as an important tool for determining legally significant statements.The article also deals with the issues of enshrining verbal offences in the criminal and administrative legislation of Ukraine. Examples of articles of the Criminal Code of Ukraine and the Code of Ukraine on Administrative Offences regulating liability for aggressive speech acts, including threats, harassment and calls for offences, are provided. It is noted that an important aspect of law enforcement is to take into account the context of statements, their content and possible consequences.The importance of further development of interdisciplinary approaches to the analysis of verbal offences is emphasised, which will allow for a more effective classification of such acts according to their semantic model. The emphasis is placed on the need to systematically consolidate the concept of ‘verbally committed offence’ in legal and scientific doctrine to ensure an adequate legal assessment of such phenomena.
Keywords: verbal aggression; legal linguistics; crime; offence; violence; harassment; legal responsibility.